2010
DOI: 10.1007/s10404-010-0627-y
|View full text |Cite
|
Sign up to set email alerts
|

Real-time monitoring of wear debris in lubrication oil using a microfluidic inductive Coulter counting device

Abstract: A microfluidic device based on an inductive Coulter counting principle to detect metal wear particles in lubrication oil is presented. The device detects the passage of ferrous and nonferrous particles by monitoring the inductance change of an embedded coil. The device was tested using iron and copper particles ranging in size from 50 to 125 lm. The testing results have demonstrated that the device is capable of detecting and distinguishing ferrous and nonferrous metal particles in lubrication oil; such partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
76
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 12 publications
0
76
0
Order By: Relevance
“…[10][11][12][13][14] For instance, for a multichannel coulter counting sensor for high-throughput detection of bioactive particles, 15 the sensitivity of the sensor is proportional to the ratio of the particle/channel size; 16 particles of different sizes need to be separated and delivered to different channels with corresponding sizes to achieve high sensitivity and high dynamic range detection. In clinical applications, the separation of rare cells from biological samples is the preconditions for subsequent diagnosis and clinical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] For instance, for a multichannel coulter counting sensor for high-throughput detection of bioactive particles, 15 the sensitivity of the sensor is proportional to the ratio of the particle/channel size; 16 particles of different sizes need to be separated and delivered to different channels with corresponding sizes to achieve high sensitivity and high dynamic range detection. In clinical applications, the separation of rare cells from biological samples is the preconditions for subsequent diagnosis and clinical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The equivalent inductance 2 of the microsensor can be described as (14) while the ferromagnetic debris is tested:…”
Section: Advances In Mechanical Engineeringmentioning
confidence: 99%
“…So the ferromagnetic debris and nonferromagnetic debris can be distinguished according to the rise or the decline of inductance, and the size of debris can be discriminated in light of the change of inductance [11,12]. The double-layer plane inductor coil and the solenoid inductor coil were adopted by Du and Zhe to detect metal debris in lubricant separately [13,14]. The experimental results indicated that the solenoid coil has a wider detection range than the double-layer plane sensor, but the sensitivity of the solenoid coil is lower than the double-layer sensor.…”
Section: Introductionmentioning
confidence: 99%
“…In a word, there are many types of contamination monitor methods such as magnetism gathering [9][10][11], inductive measurement [12][13][14], capacity detection [15,16], resistance measurement [17,18], optical method [19][20][21][22][23], acoustics detection [15,24,25] and x-ray method [26][27][28]. Among the wear debris monitor methods, ODM was used in F22 aircraft engine detection successfully.…”
Section: Introductionmentioning
confidence: 99%